2014
DOI: 10.1242/jeb.089730
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulators, stress and plasticity: a role for endocannabinoid signalling

Abstract: Any unanticipated threat to survival triggers an immediate sequence of events in the brain that culminate in a coordinated neural, endocrine and behavioural response. There is increasing evidence that stress itself modifies neural circuits. In other words, neural stress circuits learn from stress. This self-teaching is surprising as one might expect these essential circuits to be hard-wired. Our recent findings, however, indicate that repeated homotypic stress in rats causes functional changes in neural circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 79 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Retrograde eCB signaling mediates multiple forms of synaptic plasticity, such as long-term depression (LTD) or depolarizationinduced suppression of inhibition/excitation (DSI/E). Recently, the effects of stress on synaptic transmission and plasticity have become a growing area of research (reviewed in (Joels et al, 2009;Popoli et al, 2011;Senst and Bains, 2014;Bains et al, 2015). As discussed, the CB1 receptor is expressed throughout the brain and is present on glutamate and GABA synapses in stress-sensitive circuits, such as the hypothalamus, mPFC, hippocampus, and amygdala.…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 99%
“…Retrograde eCB signaling mediates multiple forms of synaptic plasticity, such as long-term depression (LTD) or depolarizationinduced suppression of inhibition/excitation (DSI/E). Recently, the effects of stress on synaptic transmission and plasticity have become a growing area of research (reviewed in (Joels et al, 2009;Popoli et al, 2011;Senst and Bains, 2014;Bains et al, 2015). As discussed, the CB1 receptor is expressed throughout the brain and is present on glutamate and GABA synapses in stress-sensitive circuits, such as the hypothalamus, mPFC, hippocampus, and amygdala.…”
Section: Functional Role Of Ecb Signaling In the Neurobiological Effementioning
confidence: 99%
“…In this case, the longterm effect on the phenotype came about through a direct effect of stressful environments on the chicks, rather than via effects of stressful environments on their mothers. Such effects could come about through routes such as early life 'programming' of the glucocorticoid and endocannabinoid systems in the brain [see Senst and Bains in this issue for details of this system (Senst and Bains, 2014)]. However, in other studies, for example in chickens, early life stress resulted in a dampening of the stress response (Goerlich et al, 2012), which has also been found in some other bird species and in rodents (Marasco et al, 2012).…”
Section: Stress Exposure and Fitnessmentioning
confidence: 99%
“…It was proposed that a tonic level of anandamide within the basolateral amygdala provides a steady-state inhibition of HPA axis activity, and that glucocorticoid-induced 2-AG release from paraventricular nucleus neurons mediates rapid negative feedback effects of glucocorticoids on the HPA axis [37]. Conversely, stress-induced HPA axis activity alters the endocannabinoid system, either positively or negatively depending on the brain region, age and conditions of stress, in several brain regions including the hippocampus, amygdala, hypothalamus, nucleus accumbens and prefrontal cortex [6,37,51]. For example, repetitive immobilization stress impaired DSI/DSE by down-regulating CB 1 receptors in the paraventricular nucleus of the hypothalamus [52], whereas chronic stress enhanced DSI partially by down-regulating MGL in the basolateral amygdala [53].…”
Section: Regulation and Plasticity Of The Endocannabinoid Systemmentioning
confidence: 99%